Teaching-learning processes in Muziki wa Injili in Dar es Salaam - Sanga, Imani (International Library of African Music, 2009)
This article is concerned with teaching-learning processes in Muziki wa Injili (Gospel Music) in Dar es Salaam, Tanzania. It discusses two methods of teaching and learning that are commonly used in Muziki wa Injili, namely, imitation and peer-directed learning.
Keywords: African Music